Application of grey wolf optimizer for optimization of fractional order controllers for a non-monotonic phase system - Verma S.K.; Nagar S.K. (My University, 2025)
In this paper, an optimized fractional order proportional-integral (FOPI), proportional-derivative (FOPD) and proportional-integral-derivative (FOPID) controllers are proposed for controlling the non-monotonic phase DC-buck regulator system. The parameters of controllers are optimized using a new meta-heuristic technique known as Grey Wolf Optimizer (GWO). Integral time absolute error (ITAE) has been taken as the fitness function for optimizing the parameters of the controller. Output response shows that the FOPI controller provides faster closed-loop performance and enhances the robustness of the system. Moreover, the FOPI controller also preserves the monotonic phase behavior of the system within the desired bandwidth. The results have validated by comparing the time domain as well as frequency domain characteristics of the system with another technique in the literature. © Springer Nature Singapore Pte Ltd. 2018.